Impact of Covid-19 Pandemics on Urology Practices and Residency Training in an Indonesian Tertiary Hospital - Kusumajaya, Christopher; Tjahjodjati, Tjahjodjati (Majalah Kedokteran Bandung, 2024)
The World Health Organization (WHO) declared Covid-19 as a global pandemic on March 11, 2020. Alterations in health service provisions must be applied to maintain prime services and decrease the number of healthcare workers exposure to Covid-19 by reducing the number of patients and workload, as well as cancelling elective surgeries. This study aimed to describe the urological services and residency training program during a Covid-19 year at Dr. Hasan Sadikin General Hospital, Bandung, which is a tertiary health center and teaching hospital in Indonesia. This was a comparative retrospective study conducted from January 2019 to December 2020 that compared the number of patients in inpatient and outpatient settings and emergency department, as well as surgical procedures performed before and during Covid-19 pandemic. Data were obtained from the administration department of the hospital, showing a reduction of 40,94%, 7.39%, 32.3%, and 53.89% of total inpatients, outpatients, emergency cases, and surgical procedures, respectively, in the urology department of the hospital when compared to the previous year. The number of surgeries that could be performed by residents was reduced by 30-60%. This current study showed the decreased number of patients and urological operative procedures during COVID-19 pandemic. This is assumed to give negative impacts to the urological residency training due to the limited exposure to variety of cases and surgical skill procedures.